Exposure of free-living Lontra longicaudis (Neotropical otter) to domestic carnivores and their associated pathogens in a protected area in Brazil - Gonchoroski, Greice Z.; Reck, Jose; Mello, Lauren S.; Silveira, Vinicius P.; Lunge, Vagner R.; Leuchtenberger, Caroline; Freitas, Thales R. O. (Frontiers in Mammal Science, 2025)
The Neotropical otter (Lontra longicaudis) is a semiaquatic mustelid widely distributed across all Brazilian biomes. However, its conservation is increasingly threatened by growing interactions with domestic animals, especially dogs and cats, which create opportunities for pathogen transmission and disease emergence in wild populations. The aim of this study was to assess the exposure of Lontra longicaudis to domestic carnivores and to pathogens associated with these species within a protected area in southern Brazil. For this, we investigated the overlapping occurrence of otters, domestic dogs, and cats in the study area, as well as the exposure to major pathogens commonly associated with dogs (Canine Distemper Virus - CDV, Canine Parvovirus type 2 - CPV, and Neospora caninum) and cats (Toxoplasma gondii and Feline Leukemia Virus - FeLV) in Neotropical otters. Samples from six otters were analyzed. Most of them presented antibodies against CDV (83%), CPV (66%), and T. gondii (66%), while none were seropositive for N. caninum or reagent for FeLV antigen. Direct observation and camera trap monitoring allowed identification of overlapping records of otters, dogs and cats. Our results indicate that Neotropical otters, even in protected areas, are exposed to domestic carnivorans and their pathogens, increasing the likelihood of disease cycles with wildlife.